The 12 week year for writers : a comprehensive guide to getting your writing done - Thrall, A. Trevor; Moran, Brian, 1959-; Lennington, Michael, 1958- (Wiley, 2021)
"Millions of people have to write for their jobs; millions want to write for their own reasons. As a result, the need for "writing skills" literature is large. Most of it falls into a few big categories: technical writing skills and references (think: Strunck and White's The Elements of Style). However, The 12 Week Year for Writers system is a writing-specific implementation of The 12 Week Year productivity system, created over many years of Thrall's use of the 12WY himself. In this book we show writers how to use the 12 Week Year system to help them increase their productivity dramatically. The 12WY for Writers system, based on the principles of the 12 Week Year and honed over many years of helping students learn to write more effectively, is a strategic operating system for writers. The system helps writers answer the most fundamental and big picture questions: What is my vision for the future? What are my writing goals? What are the best strategies and tactics to achieve those goals? How can I manage my writing process to ensure that I stay focused, productive, and on track? This book will be THE system for helping writers of all kinds and genres do a much better job planning and executing their writing and will be the only book that harnesses a proven execution system to improve the writing process. This means that our system starts with a high level of credibility and benefits from the existing reputation and name recognition of The 12 Week Year, while tailoring the system and the message to a more targeted audience."--